2017
DOI: 10.25115/ejrep.v9i25.1465
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Facebook Usage on Students’ Academic Achievement: Roles of Self-Regulation and Trust

Abstract: Introduction. This paper provides a preliminary analysis of the effects of Facebook usage by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 75 publications
(41 reference statements)
6
69
1
5
Order By: Relevance
“…Results are consistent with some studies that reported negative influences with regard to many aspects of student school performance (Rouis et al 2011;Salvation and Adzharuddin 2014;Rithika and Selvaraj 2013). Such results call for school policy makers to engage in more research to see the tradeoff between the various advantages and disadvantages of using specific social media applications.…”
Section: Discussionsupporting
confidence: 81%
“…Results are consistent with some studies that reported negative influences with regard to many aspects of student school performance (Rouis et al 2011;Salvation and Adzharuddin 2014;Rithika and Selvaraj 2013). Such results call for school policy makers to engage in more research to see the tradeoff between the various advantages and disadvantages of using specific social media applications.…”
Section: Discussionsupporting
confidence: 81%
“…The researcher determines in the study conducted on 506 secondary school students that attitudes of the students towards reading, levels of understanding what is read and number of words per minute with silent reading decrease as Facebook addictions of the students increase. These findings are actually in parallel with the result that Facebook use affects academic success (Akdemir, 2013;Kuss & Griffiths, 2011;Rouis et al 2011). Moreover, Türkyılmaz (2012bTürkyılmaz ( , 2014 determined that use of mass media affected attitude towards reading negatively.…”
Section: Discussion Conclusion and Implementationsupporting
confidence: 77%
“…Park et al (2014) showed that the Asian students who study in the United States and use Facebook have a higher level of psychological well-being than those who do not use any type of social network or those who utilize ethnic social networks (that is, more typical of their language or their country).Facebook use requires a certain degree of self-regulation or self-control, as is especially highlighted by two works. Rouis et al (2011) argue that students with a self-regulation capacity can limit the amount of time that they invest in Facebook and, therefore, its use will not impact negatively on their academic performance. Furthermore, 2 papers focus on the connection between Facebook and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 5 papers relate the utilization of Facebook as a teaching instrument to the degree of satisfaction achieved thanks to this experience. For example Rouis et al (2011) established as hypothesis that using Facebook increases the level of satisfaction with life because it represents a modern form of activity typically associated with leisure and because it is a communication tool that students often use to keep in touch with their friends and relatives. Similarly in Brazil, Oliviera and Huertas (2015) find out that Life Satisfaction influence on We-Intention is mediated by Subjective Norm, Group Norm, Social Identity, Entertainment Value, and Maintaining Interpersonal Interconnectivity including Facebook.…”
Section: Topics Analyzedmentioning
confidence: 99%